(3CdajI GHf eGdcs - (3GdWGFj, GdCfOdSj, GdLjGfj, GHf eGdc, LeGd GdOjf, eMeO Hf YHO Gddg Hf eGdc, J (B672 (3g`s
(3ChdgG (B:s
.. (3heYQH GdCSeGA eG bO SdeG ef THg MQa cCQV hSeG (B** (3haYd CeQ eVi HfjG hCYQHhG eVGQYG Ef CYQHG (B*** (3ef fhf JhcjO eHGTQ hef fhf GfGK cjQYf ef aJf (B...s
(3BNQgG (B:s
.. (3hJOZe GdjGA ajg hGdhGh Ef eG bHd hGh Ve aCcQ Hgf (B*** (3hCda Sde haj GdebUhQ Yf gRjd GfbdG HgG jGA MSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\233s
(3cTa GdXfhf (B1\ 152s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs